Effect of Using Habits of Cell Phone on the Study of the Students: A Case Study on Parents and Teachers of Sargodha City - Amin , Salman; Rashed, Adnan; Umair, Atif (Asian Journal of Empirical Research, 2014)
This study is an effort to investigate the “Impacts of Cell Phone Using Habits on the Studies of Students of University of Sargodha and Punjab University Lahore. The study used the survey method for data collection. A sample of 100 respondents consisting of 50 Teachers and 50 Parents was selected by using purposive and convenience sampling technique. The findings show that respondents frequently use cell phone and overwhelming majority spent lots of money in their daily lives. Respondents frequently use cell phone to contact with parents followed by friends, close friends whereas somewhat with classmates and rarely with teachers. But according to teachers and parents students mostly use cell phone to contact with parents; classmates, friends, and close friends with little difference. Students frequently use cell phone in class room not for lecture recording but for the purpose of SMS texting etc. It is also observed that students mostly use cell phone for un-educational activities and according to teachers and parents due the use of cell phone respondents are losing focus on their studies and parents are decreasing their parental control on their children due to the use of cell phone.